A clinical analysis on 40 cases of spontaneous intracranial hypotension syndrome. (2nd January 2019) - Li, Cun; Raza, Hafiz Khuram; Chansysouphanthong, Thitsavanh; Zu, Jie; Cui, Guiyun
Abstract: Objective: To investigate clinical and imaging features of 40 patients with spontaneous intracranial hypotension (SIH). Methods: 40 cases of spontaneous intracranial hypotension (SIH) diagnosed in our hospital from June 2013 to September 2017 were collected and retrospectively analyzed. Results: In our study, the male to female ratio was 2:3. The average age of onset was 43.0 ± 15.0 years. There were 12 (30.0%) patients with clear incentives, mostly catching cold. The average length of hospital stay was 11.2 ± 6.3 days. All the patients showed orthostatic headaches, 62.5% patients with nausea or vomiting, 40.0% patients with neck stiffness, 17.5% patients with dizziness and vertigo, 10.0% patients with numbness and weakness of limbs, 5% patients with neck discomfort, and 2.5% patients with visual symptoms (visual impairment, photophobia, diplopia). 24 patients underwent CT scans which showed no abnormalities in 20 cases (83.3%), subdural fluid accumulation in 3 cases (12.5%), and subdural haematoma in 1 case (2.5%). Cranial contrast-enhanced MR scans showed diffuse pachymeningeal enhancement (95.83%, 23/24), signs of pituitary hyperaemia in 5 cases (20.8%), subdural fluid accumulation and subdural hematoma in 4 cases (16.7%), sagging of the brain in 3 cases (12.5%), and engorgement of venous structures in 1 case (4.1%). Six patients underwent plain and contrast-enhanced spinal MR scans which showed varying degrees of dural thickening and enhanced performance in all the patients. 92.5% (37/40) of patients had cerebrospinal fluid pressure <60 mmH2 O on lumbar puncture. 97.5% of patients underwent conservative treatment with drugs and had a good outcome. Conclusion: Orthostatic headache and cranial MRI diffuse pachymeningeal enhancement are characteristic features of SIH. Cranial contrast-enhanced MR scan is recognized as the first and non-invasive investigation in the diagnosis of SIH. Most patients had cerebrospinal fluid pressure <60 mmH2 O. The vast majority of patients improved with fluid replacement.